Immoral Obscenity: Censorship of Folklore Manuscript Collections in Late Stalinist Estonia - Kaisa Kulasalu (Journal of Ethnology and Folkloristics)
The history of folkloristics contains many cases of obscene materials that were excluded from field notes, books and archives. The Estonian Folklore Archives (founded in 1927) did incorporate dirty jokes, riddles and songs in its collection. Soviet occupation changed the topics of folklore scholarship and archival practices. Between the years 1945 and 1952, the Folklore Archives’ manuscript collections, catalogues and photographs were censored. Anti-Soviet texts were cut out or made unreadable. In the first years after the incorporation of the Republic of Estonia into the Soviet Union, anti-Soviet mainly meant politically sensitive materials such as jokes about Stalin, very patriotic texts or the names of some people. During the beginning of the 1950s, stricter rules were applied and obscene texts were also censored. In this article, I will focus on the censorship of obscene words and motifs and the political dimension of moralistic censorship in a totalitarian state.